Точка обмана: роман / Дэн Браун - Браун Дэн (Серия "Интеллектуальный детектив", 2005)
Экземпляры: аб. (2008) / Инвентарный номер: 52159 / Цена: / Сис.шифр: 84(7Сое)-44 / Авт.знак: Б 87 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44